ANALISIS RESPON PELAKU USAHA WARUNG MAKAN TERHADAP KEWAJIBAN SERTIFIKASI HALAL DI KABUPATEN PAMEKASAN - FAQIH, AHMAD SULAIMAN FAQIH (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2021)
ABSTRACT Basically, everything that is done has a purpose, where that goal can be achieved after carrying out the activity. Likewise, this research activity also has a goal to be achieved. The purpose of this study is to find out how the response of food stall businesses to the obligation of halal certification in Pamekasan Regency and what are the inhibiting factors in carrying out halal certification. Not only that, this research is also expected to provide knowledge and thoughts of the wider community in realizing halal certification in accordance with Islamic teachings. This research was carried out using a qualitative descriptive research method in which the data was collected by interviewing informants (food stall actors) as a source of information. The results of the study show that it is halal for food stall business actors. The average food stall business actor perceives that halal certification is not too important for food stall business actors because it does not affect their sales. They also feel burdened with the obligation of halal certification because the requirements, especially the costs incurred are not commensurate with their income. Keywords: Response; Halal Certification; Food stalls